Pharmacy practice and education in Nigeria - Abiola, Hassan Olatunde; Nikoleishvili, Elza (Caucasus Journal of Health Sciences and Public Health, 2018)
Pharmacy practice and education in general—as well as the availability, affordability, and accessibility of quality, safe, and effective essential medicines—are critical to the success of a health care delivery system. Since the 1990s, pharmacy practice and education in Nigeria have changed considerably. Pharmacy education in the country has undergone a modest transformation from a science-based curriculum to a blended science- and practice-based curriculum. In recent studies conducted by the ministry of health in Nigeria shows the historical development of pharmacy education from one school of pharmacy in the 1920s to about twenty schools 40 years later. Nigeria has a population of over 160 million and there are 129 universities in Nigeria comprising 40 federal, 38 State, and 51 private universities accredited by the NUC. In which 40 of them are accredited to study and practice pharmacy, The study also looked at the continuous efforts made to produce the pharmacist with the requisite competency for the ever-changing roles in meeting the dynamic and varied needs of patient. Through the emergence of pharmaceutical care and collaborative drug therapy management globally, pharmacists in Nigeria have equally started engaging in patient-centered care with other health professionals as a team. Achievements and challenges during the last two decades are described. Considering the recommendations and ways forward, there is a need to promote inter-professional education and collaborative care at various levels, with an aim to harness the mutual integration and respect of health professionals into the healthcare processes to benefit patients and the health system. The potential for pharmacists to be involved in public health intervention programs remains largely untapped. Conclusively, chaotic drug distribution system, professional complacency and conservatism, extrinsic system failures, and inadequate human resources for health remain challenging in Nigeria's pharmaceutical sector and the healthcare system. In the future, progressivity in developmental growth could augment rapid extension of pharmacy education and practice related to the increasing number of pharmacy graduates and pharmacists, use of information and technology system, and expansion of clinical and nonclinical services offered by pharmacists. Evidence-based information for policymaking and implementation might assist in advancing the pharmacy profession and practice in the country.